IMMUNE RESPONSE TO ESCHERICHIA COLI IN PIGLETS THAT GIVEN ESCHERICHIA COLI – AVIAN INFLUENZA RECOMBINANT VACCINE - Maranata, Pieter Mbolo; Mahardika, I Gusti Ngurah Kade; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2022)
Escherichia coli as a cause of colibacillosis is an important disease in pig farms because it causes weight loss, death in pigs, and significant economic losses. Handling colibacillosis by using antibiotics can cause a resistance effect, so we need an alternative to using a vaccine. The latest vaccine development by Udayana University using E. coli isolates from the Bali area was carried out to use this problem. Research on immunization against E. coli in piglets who have been given a recombinant vaccine E. coli - Avian Influenza. The sample used in this study was serum from 12 piglets. In this study, the sample was divided into two groups, namely the treatment group with vaccines and the control group without vaccine assistance. The group was given the vaccine at age of 1 week and repeated at age of 3 weeks, and the serum from both of groups was taken when the pigs were 4 weeks old. The serum is then tested using an Enzyme-Linked Immunosorbent Assay (ELISA) serological test. The results showed a varying optical density figures, the study group had an average optical density of 1.010 and the control group had an average of 0.418. Analysis statistic using the unpaired t-test, the two groups had significant differences. The level of antibodies against E. coli in vaccinated piglets is higher than the level of antibodies against E. coli in unvaccinated piglets. Diarrhea case data is used as supporting data that shows significant differences in the group given the booster vaccine in the third week. In the fourth week of the vaccination group, no piglets were diarrhea, while in the unvaccinated group 4 diarrhea was taken. The conclusion that were an increase in the immune response in pig that given the recombinant vaccine E. coli rather than control group.